Perfil epidemiológico em saúde bucal do Município de Alagoinha-PB - Costa, Camila Helena Machado da (2011)
The aim of this study was to determine the prevalence of caries and treatment needs and verify acess and evaluation of dental services, as well the degree to which oral health affects the daily performance between the age groups of 5, 12, 15 to 19, 35 to 44 and 65 to 74 years in Alagoinha, PB, Brazil. Data collection was conducted in eight urban census tracts in the city, using the methodology of SB BRASIL 2010. Through the cartographic map of the city, the sectors were recorded by a trained examiner (kappa = 0.92 95% IC 0.90 to 0.95). Clinical examination was performed on 316 individuals and 371 responded to interview and intra-examiner was assessed using the kappa test (0.97). Index Oral Impacts on Daily Performances (OIDP) was used to assess the impact on oral daily performance. Once collected, the data were worked by descriptive statistics and tested using Chi-square and Fisher Exact test. The prevalence of dental caries between age groups was 86.1%, the dmft for 5 years and DMFT at 12 was 1.76 and 2.17, respectively. According to the type of treatment need in all age groups, the highest percentage corresponded to the indication of restorations. There was a statistically significant difference (p<0.05) compared to the presence of caries experience and gender, dental visits and interference in daily activities. Of the total, 12.4% reported never having been to the dentist and among those who were public service was the most sought and the main reason for seeking service was the treatment and tooth extraction. Of the respondents, 62.8% had at least one daily performance affected by dental problems. There was a statistically significant difference between the presence of impact of oral health in relation to a toothache, dental visits, need for prosthesis and dental caries experience (p <0.005). It is concluded that there is an unmet demand for dental treatment, is important to establish public policies reorient health services for the provision of oral health care and health promotion.that measures aimed at preventing and treating this population.